Modelling and Manufacturing of Progressive die for Mechanical Press Operations - et.al, V.Venkatrami Reddy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A progressive die is a type of die in which multiple operations performed in a single stroke, which was mostly used in sheet metal operations. The working process of sheet metal is widely used in all manufacturing industries such as mechanical, defense and automotive etc. The key advantage of metal working process involves enhancement of production rate and cost reduction. This paper is aimed to develop a multi-functional die which can perform simultaneously both punching and blanking operations in one stroke. The present work is mainly focused on modeling and manufacturing of the die components, where PRO-E was used for modelling and FANUC controlled CNC machine was used to execute and prepared part program.